2022
DOI: 10.6007/ijarbss/v12-i13/14147
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role Technology Adoption in the Relationship Between Financial Factors and Economic Well-Being in Agricultural Context

Abstract: Due to the inadequacy of the related research, the key objective of this research is to determine the impact of financial antecedents on growers' agricultural technology adoption and economic well-being. A cross sectional survey was carried out among Sri Lankan coconut growers who were chosen through the multi stage random sampling procedure. Based on the PLS-SEM results, all the direct associations between financial factors (financial knowledge, financial behaviour), and economic well-being were accepted. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…A number of empirical research have found a statistically significant relationship between financial behavior, and economic well-being (Wijekoon et al, 2021a;2021b;2021c). The positive correlation between financial behavior, and economic well-being was further confirmed by the results of this study.…”
Section: Direct Effectssupporting
confidence: 83%
“…A number of empirical research have found a statistically significant relationship between financial behavior, and economic well-being (Wijekoon et al, 2021a;2021b;2021c). The positive correlation between financial behavior, and economic well-being was further confirmed by the results of this study.…”
Section: Direct Effectssupporting
confidence: 83%
“…Moreover, the adoption of agricultural technology was found to mediate the relationship between financial factors and economic well-being. This study suggests that improving financial knowledge and behavior can enhance technology adoption and, consequently, economic well-being in the agricultural sector [8].…”
Section: The Landscape Of Agricultural Economicsmentioning
confidence: 81%
“…The study found that financial factors such as financial knowledge and behavior have a direct impact on economic well-being. Moreover, technology adoption was found to have a significant mediating effect between financial factors and economic well-being [8].…”
Section: Introductionmentioning
confidence: 96%